311 The Sigma-Receptor-Agonist 4-Phenyl-1-(4-Phenylbutyl) Piperidine (PPBP) Decreases Neonatal Excitotoxic Brain Injury and Diminishes Microglial Cell Activation. (October 2012) - Wegleiter, K; Lippert, N; Posod, A; Neubauer, V; Urbanek, M; KiechlKohlendorfer, U; Griesmaier, E
Abstract : The pathogenesis of perinatal brain injury is multifactorial. In animal models of adult brain injury the sigma-1-receptor agonist 4-phenyl-1-(4-phenylbutyl) piperidine (PPBP) was shown to be neuroprotective due to modulation of inflammatory and apoptotic pathways and affection of excitotoxic signaling cascades. In the current study we evaluated the effect of PPBP in a neonatal animal model of excitotoxic brain injury. We performed an intracranial injection of ibotenate in CD1 mice on postnatal day 5 (P5) to induce excitotoxic injury. A single injection of vehicle or PPBP, in a dosage of 1, 5 or 50 µg/g body weight, was applied intraperitoneally one hour after the insult. Primary study endpoints were evaluated 24 (P6) and 120 (P10) hours after the insult by analysis of lesion size, number of cells stained positively for cleaved caspase-3 and isolectin B4. Systemic application of PPBP resulted in a significant reduction of lesion size in cortical gray matter in all dosages (p<0.05). and underlying white matter in 1 and 50µg/g (p<0.05) at P10. At P6 microglial cell activation was significantly diminished by PPBP in cortical gray (p<0, 001) and underlying white matter (p<0.05). Lesion size on P6 and number of cells stained positively for activated caspase-3 at P6 was not affected by the treatment (p>0.05). In this neonatal animal model we were able to demonstrate a beneficial effect of the sigma-1 receptor agonist PPBP. This data suggest that PPBP may be a potential therapeutic approach in neonatal brain injury.